The co-creation of value for pursuing a sustainable happiness: The analysis of an Italian prison community. (June 2021) - Cosimato, Silvia; Faggini, Marisa; Prete, Marzia del
Abstract: Happiness is generally considered a timeless and an ultimate goal for human being, groups, and even nations. Even though the personal dimension of happiness has been widely investigated, the literature still calls for further research on how individual, community and/or global happiness can be enhanced and sustained in the long run without exploiting future generations possibility to be happy. Thus, this study aims at contributing to bridge this gap, embracing value co-creation and its circular logic as a guiding framework of analysis. To this end, the existing relationship between happiness, co-creation and sustainable development has been explored according to the Public Service Logic (PSL), a theoretical framework based on the well-established construct of value co-creation. To support the theoretical investigation, an extreme case study has been analysed, underlining the way a specific Italian prison community approaches individual and collective happiness, both currently and in the future. The results paved the way for some interesting managerial and policy implications that might stimulate policymakers in carrying out sustainable actions and programs open to the participation and the active contribution of citizens. In this sense, the present study represents one of the first attempts to approach happiness as one of the determinants of sustainable development. Highlights: Even though happiness is a timeless goal for each human being, group, and even nation, little research has been dedicated to better define it and to understand how it can be sustained in the long-term. This work aims at contributing to better define the still vague sustainable happiness. Embracing the value co-creation framework, sustainable happiness emerges from the willingness of socio-economic actors to share their resources for co-creating value for all the involved party. The analysis provided some interesting implications for policymakers.